Answer:
The only difference is that we line up the numbers according to the decimal point. For addition, it doesn't matter which number goes on the bottom.
Let's say the first number is "a"
the next consecutive can just be "a+1" and the next, you guessed it, "a+2"
the two smaller ones are a and a+1, the larger one is a+2
now, the product of "a" and "a+1" equals 5 times "a+2" but less by 5
thus a(a + 1) = 5(a + 2) - 5 <----- solve for "a"
The area is 20
The height is 5
The volume is 60
The surface area is 94
The correct answer is: [D]: "17" .
______________________________________________________
The radius is: " 17" .
______________________________________________________
Note:
______________________________________________________
The formula/equation for the graph of a circle is:
______________________________________________________
(x − h)² +<span> </span> (y − k)² = r² ;
in which:
" (h, k) " ; are the coordinate of the point of the center of the circle;
"r" is the length of the "radius" ; for which we want to determine;
_______________________________________________________
We are given the following equation of the graph of a particular circle:
_______________________________________________________
→ (x − 4)² + (y + 12)² = 17² ;
which is in the correct form:
→ " (x − h)² + (y − k)² = r² " ;
in which: " h = 4 " ;
" k = -12" ;
"r = 17 " ; which is the "radius" ; which is our answer.
→ { Note that: "k = NEGATIVE 12" } ;
→ Since the equation <u>for this particular circle</u> contains the expression: _________________________________________________________
→ "...(y + k)² ..." ;
[as opposed to the standard form: "...(y − k)² ..." ] ;
_________________________________________________________
→ And since the coordinates of the center of a circle are represented by:
" (h, k) " ;
→ which are: " (4, -12) " ; (<u>for this particular circle</u>) ;
_________________________________________________________
→ And since: " k = -12 " ; (<u>for this particular circle</u>) ;
_________________________________________________________
then:
" [y − k ] ² = [ y − (k) ] ² = " [ y − (-12) ] ² " ;
= " ( y + 12)² " ;
{NOTE: Since: "subtracting a negative" is the same as "adding a positive" ;
→ So; " [ y − (-12 ] " = " [ y + (⁺ 12) ] " = " (y + 12) "
___________________________________________________
Note: The above explanation is relevant to confirm that the equation is, in fact, in "proper form"; to ensure that the: radius, "r" ; is: "17" .
___________________________________________________
→ Since: "r = 17 " ;
→ The radius is: " 17 " ;
which is: Answer choice: [D]: "17" .
___________________________________________________